Grinding-Assisted Synthesis of Some Heterocyclic Compounds - Abdullah, Jasim Ali; Rabeaa, Muwafaq Ayesh (Asian Journal of Chemistry, 2020)
This article involves synthesis of some heterocyclic compounds from an amine derivative using eco-friendly approach (grinding). The first step involves synthesis of Schiff base from benzaldehyde derivatives (3-hydroxybenzaldehyde and 4-nitrobenzaldehyde) with 4-aminoantipyrine. These compounds were used as precursor for the synthesis of heterocyclic compounds and then synthesized tetrazole, oxazepine oxazepane derivatives from Schiff base with sodium azide, phthalic anhydride, maleic anhydride and succinic anhydride, respectively. The heterocyclic compounds were characterized by TLC, melting point, FTIR, 1H NMR, 13C NMR, GC-mass and HRMS analyses.